ANALISIS IMPLEMENTASI PROGRAM KELUARGA HARAPAN (PKH) BIDANG PENDIDIKAN DI KECAMATAN TEGAL TIMUR, KOTA TEGAL - Diastuti, Juning; Santoso, R. Slamet; Hanani, Retna (Jurusan Administrasi Publik, Fakultas Ilmu Sosial dan Ilmu Politik, Universitas Diponegoro, 2021)
Program Keluarga Harapan (PKH) is a program of providing conditional social assistance to poor families (KM) who are designated as beneficiary families with purpose to improve the standard of living of Beneficiary Families (KPM) through access to education, health and social welfare services.In policy implementation, there are factors that determine the success of a policy implementation. The purpose of this research is to know magnitude the correlation between resources and the compliance of target groups in the implementation of Program Keluarga Harapan (PKH). The method used is a quantitative method with a questionnaire. The results showed that there was a positive and significant correlation between resource variables and target group compliance with PKH implementation. Resources have a positive correlation with PKH implementation of 38.2%. The compliance of the target group has a positive correlation with PKH implementation of 11.8%. Resources and target group compliance together have a significant correlation with PKH implementation of 37.6% while the remaining 62.4% is explained by other variables not in this research. Therefore, further research is needed by using variable communication and disposition of program implementers.